Histological Regression of Giant Cell Tumor of Bone Following RANK Ligand Inhibition - Martin F. Dietrich MD, PhD; Dominick Cavuoti MD; Michael Landay MD; Yull E. Arriaga MD (SAGE Publishing, 2014)
Lung metastases are a rare complication of giant cell tumors of bone. We herein describe an interesting case of histological regression and size reduction of lung metastases originating from a primary giant cell tumor of bone in response to the RANK ligand inhibitor denosumab.